15-3 (x-2) +6=10 answers me
Answers
Answered by
1
Answer:
hope this may help u
pls thank my answers
Attachments:
![](https://hi-static.z-dn.net/files/d87/e7a895941b2f1730d95d982aef2e3411.jpg)
Answered by
0
Answer:
x = 17/3
Step-by-step explanation:
15 - 3 ( x - 2 ) + 6 = 10
Step 1: Simplify both sides
15+(−3)(x)+(−3)(−2)+6=10(Distribute)
15+−3x+6+6=10
(−3x)+(15+6+6)=10(Combine Like Terms)
−3x+27=10
−3x+27=10
Step 2: Subtract 27 from both sides.
−3x+27−27=10−27
−3x=−17
Step 3: Divide both sides by -3.
−3x/-3 = -17/ -3
x = 17/3
Similar questions